Maimonides in his world portrait of a Mediterranean thinker - Stroumsa, Sarah (Princeton, N.J. : Princeton University Press, 2009)
"While the great medieval philosopher, theologian, and physician Maimonides is acknowledged as a leading Jewish thinker, his intellectual contacts with his surrounding world are often described as related primarily to Islamic philosophy. Maimonides in His World challenges this view by revealing him to have wholeheartedly lived, breathed, and espoused the rich Mediterranean culture of his time." "Sarah Stroumsa argues that Maimonides is most accurately viewed as a Mediterranean thinker who consistently interpreted his own Jewish tradition in contemporary multicultural terms. Maimonides spent his entire life in the Mediterranean region, and the religious and philosophical traditions that fed his thought were those of the wider world in which he lived. Stroumsa demonstrates that he was deeply influenced not only by Islamic philosophy but by Islamic culture as a whole, evidence of which she finds in his philosophy as well as his correspondence and legal and scientific writings. She begins with a concise biography of Maimonides, then carefully examines key aspects of his thought, including his approach to religion and the complex world of theology and religious ideas he encountered among Jews, Christians, Muslims, and even heretics; his views about science; the immense and unacknowledged impact of the Almohads on his thought; and his vision of human perfection." "This insightful cultural biography restores Maimonides to his rightful place among medieval philosophers and affirms his central relevance to the study of medieval Islam."--BOOK JACKET.
Maimonides and Mediterranean culture -- Mediterranean cultures -- Maimonides as a Mediterranean thinker -- Horizons -- Transformations in the Jewish world -- Maimnonides and Saadia -- The theological context of Maimonides' thought -- Islamic theology -- Heresies, Jewish and Muslim -- An Almohad "fundamentalist"? -- Almohads -- Maimonides and the Almohads -- Legal aspects -- Theology -- Exegesis and political philosophy -- Philosophy and astronomy -- Conclusion -- La longue durée : Maimonides as a phenomenologist of religion -- Sabians -- Maimonides as an historian of religion -- "A wise and understanding people?" : the religion of the people -- A critical mind : Mamonides as scientist -- Medicine and science -- "Ravings" : Maimonides' concept of pseudo-science -- "From Moses to Moses" : Maimonides' vision of perfection -- "True felicity" : the hereafter in Maimonides' thought -- Issues of life and death : the controversy regarding resurrection -- "Gates for the righteous nation" : the philosopher as leader.
Includes bibliographical references (p. [193]-217) and index.
Description based on print version record.
Keywords: Maimonides, Moses, -- 1135-1204.; Philosophy, Medieval; Intellectual life -- History; Maimonides, Moses; Electronic books; PHILOSOPHY / Eastern